Expand: (2x+3y-4)(x-2y-3) Topic: Math 1 Answer | Add Yours rcmath | High School Teacher | (Level 1) Associate Educator Posted on April 18, 2012 at 5:19 PM (Answer #1) `(2x+3y-4)(x-2y-3)=` `2x*x+2x*(-2y)+2x*(-3)+3y*x+3y*(-2y)+3y*(-3)-4*x-4*(-2y)-4*(-3)=` `2x^2-4xy-6x+3xy-6y^2-9y-4x+8y+12=` `2x^2-6y^2-xy-10x-y+12` We’ve answered 396,016 questions. We can answer yours, too. Ask a question

rcmath | High School Teacher | (Level 1) Associate Educator Posted on April 18, 2012 at 5:19 PM (Answer #1) `(2x+3y-4)(x-2y-3)=` `2x*x+2x*(-2y)+2x*(-3)+3y*x+3y*(-2y)+3y*(-3)-4*x-4*(-2y)-4*(-3)=` `2x^2-4xy-6x+3xy-6y^2-9y-4x+8y+12=` `2x^2-6y^2-xy-10x-y+12`